EFEKTIVITAS METODE MULTIMEDIA LEARNING BERBASIS MEDIA VISUAL DAN DIGITAL UNTUK MENINGKATKAN PEMAHAMAN SISWA TENTANG PERILAKU ANTI BULLYING DI UPT SDN 172 ENREKANG - Muh. Ade Nur Ilham; M. Yunus Sudirman; Ahmad Kamil; Fitriyanti Sulaiman; Muh Idham Haliq (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Character education is an important aspect in shaping students' personalities, including instilling anti-bullying behavior from an early age. The phenomenon of bullying among elementary school students remains a serious problem that affects students' psychological conditions and learning processes. UNESCO data (2022) shows that around 246 million children and adolescents worldwide experience bullying every year, with a higher prevalence in developing countries such as Indonesia. Data from the Indonesian Child Protection Commission (KPAI) and the Indonesian Teachers Federation (FSGI) recorded 226 bullying cases in 2022, consisting of physical bullying (55.5%), verbal bullying (29.3%), and psychological bullying (15.2%). Based on observations at UPT SDN 172 Enrekang, students’ understanding of anti-bullying behavior was still relatively low, so innovative learning methods were needed. This study used a quantitative approach with a Pre-Experimental Design using the One Group Pretest-Posttest design. The research sample consisted of 18 students from class VB selected through the total sampling technique. Data collection was conducted through questionnaires (pretest and posttest) consisting of 25 Likert-scale statement items. The instrument was validated by experts; all items were declared valid (r-count > 0.468), and the Cronbach’s Alpha value was 0.946. The data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, and the N-Gain test. The results showed an improvement in students’ understanding after the treatment. The average pretest score of 67.11 increased to 93.11 in the posttest. The average N-Gain value of 0.8345 was categorized as high (≥ 0.7). Multimedia learning methods based on visual and digital media were effective in improving students’ understanding of anti-bullying behavior at UPT SDN 172 Enrekang.